The Subtle Tyranny of Men: Lucy Honeychurch’s Resistance of Edwardian Society’s Limitations on Women in A Room with a View - Sitompul , Siska Febriana; Rizano, Gindho; Yeni, Marliza (LingoLitera, 2025)
This article aims to show and explain how the limitations on women during the Edwardian era in E. M Forster’s book A Room with a View. The historical approach helps the authors in analyzing the main problem of the book and how it happened during the years of the Edwardian period. It is library research using written materials as the main data to complete the article. The result of this research shows that women were struggling to fight for their rights. This struggle leads to the resistance of women to be able to be free as men, challenging traditional norms in British society. This article highlights the struggle for gender equality in Edwardian England, exemplified by historical sacrifices and Lucy Honeychurch’s defiance of societal norms in A Room with a View.